Solution Complexation of Amino Acidate Zwitter Ion with Uranyl(VI): Electrophoresis and pH-metric Studies. - BAPNA , R.; VYAS, P.C.; ARORA, M.; GUPTA., R. (Asian Journal of Chemistry, 2010)
Paper electrophoretic investigation of uranyl complexes with amino acids (L-threonine, L-Ieucine, L-asparagine, DL-β-phenyl alanine) have been carried out in 0.1 M KNO3 solution at 35°C and 3.5 pH, to elucidate the nature of coordination in these complexes. Electrophoretograms are supportive of coordination through carboxylate group of the amino acidate zwitter ion. The relative mobilities and stabilities of the complexes are reported. The results are supplemented with pH-metric studies.